Social and Economic Impact of Converting Productive Agricultural Land Into Housing in West Lombok - Muh. Harmoko; Ibrahim (CV. GovPlan Indonesia, 2026)
The conversion of productive agricultural land into residential areas in various regions, including West Lombok, has given rise to a variety of social and economic problems triggered by the lack of evaluation of facilities before the conversion was carried out. The main problem in this study is the unpreparedness of basic infrastructure, which has an impact on the decline in the quality of social services, changes in livelihoods, and the weakening of the economic resilience of the local community. This study aims to analyze the effect of infrastructure evaluation (X₁) and the conversion of productive agricultural land (X₂) on the socioeconomic impact on the community (Y). The research method used a correlational quantitative approach with 20 respondents, using a Likert scale questionnaire consisting of 18 statements. Data analysis was conducted through descriptive statistics and multiple linear regression. The results show that both independent variables simultaneously have a significant effect on Y, as evidenced by an F value of 6.489 and p = 0.008. The R² value of 0.433 indicates that 43.3% of the variation in the socio-economic impact on the community can be explained by infrastructure evaluation and land conversion. These findings confirm that the lack of basic facilities and the high rate of land conversion exert real pressure on the socioeconomic conditions of the community, thus requiring the strengthening of facility evaluation policies and spatial utilization control to support more sustainable housing development